Listening and Hearing: A Voice Hearer's Invitation into Relationship - Britz, Berta (Frontiers in Psychology, 2017)
Although historically overlooked, empirical links between trauma and psychosis have received growing attention over the past decade. Increasingly, clinical researchers have also zeroed in on the role that distressing or traumatic life events play in the psychosocial formation and maintenance of psychosis. This paper re-locates anomalous experiences in their human contexts, and asks that clinicians and researchers engage with these contexts. The author shares a first person account of her experience changing her relationships with dominance in order to reclaim and accept her human being-ness, a reorientation supported by her involvement in the world hearing voices network movement and community. I call for mental health systems, providers and researchers to collaborate with the persons at the center of their work—to dare to listen, hear, and connect for mutual learning, healing and wholeness. The article concludes with recommendations and a rallying call for services to be made more inclusive and to re-center in meaningful collaboration with people with lived experience. More comprehensive, meaningful and accountable practices can be co-created when people are met equally as human subjects, both responsible and accountable for change.